Maladaptive modifications in myofilament proteins and triggers in the progression to heart failure and sudden death - Yar, Sumeyye (2014)
In this review, we address the following question: Are modifications at the level of sarcomeric proteins in acquired heart failure early inducers of altered cardiac dynamics and signaling leading to remodeling and progression to decompensation? There is no doubt that most inherited cardiomyopathies are caused by mutations in proteins of the sarcomere. We think this linkage indicates that early changes at the level of the sarcomeres in acquired cardiac disorders may be significant in triggering the progression to failure. We consider evidence that there are rate-limiting mechanisms downstream of the trigger event of Ca(2+) binding to troponin C, which control cardiac dynamics. We discuss new perspectives on how modifications in these mechanisms may be of relevance to redox signaling in diastolic heart failure, to angiotensin II signaling via β-arrestin, and to remodeling related to altered structural rigidity of tropomyosin. We think that these new perspectives provide a rationale for future studies directed at a more thorough understanding of the question driving our review.